2020
DOI: 10.1097/gox.0000000000003027
|View full text |Cite
|
Sign up to set email alerts
|

Median Nerve Neuropathy following Radial Forearm Free Flap Phalloplasty: A Case Report

Abstract: Summary: As the transgender population increases, gender-affirming surgeries are being performed at unprecedented rates. Despite this increase, complications and long-term outcomes of gender-affirming interventions are largely understudied. We present a transgender patient who underwent radial forearm free flap (RFFF) phalloplasty as part of gender affirmation. Immediately following surgery, the patient reported paresthesia in the donor arm in the median nerve distribution followed by a neuropathic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Pain in this region may also result from radiation delivered to the brachial plexus, 39 especially via intensity‐modulated radiotherapy 40 . We also found that patients reported lower back and lower extremities as sites of pain, which may be related to arthritis or alternatively, may have been sites for flap reconstruction surgery which has been associated with neuropathy 72–74 . Additional studies are needed to validate our findings.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Pain in this region may also result from radiation delivered to the brachial plexus, 39 especially via intensity‐modulated radiotherapy 40 . We also found that patients reported lower back and lower extremities as sites of pain, which may be related to arthritis or alternatively, may have been sites for flap reconstruction surgery which has been associated with neuropathy 72–74 . Additional studies are needed to validate our findings.…”
Section: Discussionmentioning
confidence: 54%
“…40 We also found that patients reported lower back and lower extremities as sites of pain, which may be related to arthritis or alternatively, may have been sites for flap reconstruction surgery which has been associated with neuropathy. [72][73][74] Additional studies are needed to validate our findings. We found that use of analgesia among HNC survivors was low, especially among those with NP, but that those with NP reported higher intake of opioid analgesics.…”
Section: Discussionmentioning
confidence: 78%
“… 7 Nerve damage due to tourniquet application has been shown to emerge from either direct nerve compression or ischemia, particularly if it is applied for more than 3 hours. 8 Thus, alternating the arm used for monitoring blood pressure and decreasing the circle time for patients undergoing prolonged procedures might help reduce the likelihood of such occurrences. Patient positioning in theater also plays a crucial role in the development of compression injuries.…”
Section: Discussionmentioning
confidence: 99%
“…Gender dysphoria is a mismatch between physical sex and psychological gender identity. Gender‐affirming surgeries and hormone therapies are currently increasing, but long‐term outcomes of these therapies are largely understudied 2 . Although both CIDP and gender dysphoria can severely affect the quality of life, little is known about their relationship.…”
Section: Introductionmentioning
confidence: 99%